2023
DOI: 10.1111/cns.14112
|View full text |Cite
|
Sign up to set email alerts
|

Dl‐3‐n‐butylphthalide promotes synaptic plasticity by activating the Akt/ERK signaling pathway and reduces the blood–brain barrier leakage by inhibiting the HIF‐1α/MMP signaling pathway in vascular dementia model mice

Abstract: Aims DL‐3‐n‐butylphthalide (NBP) exerts beneficial effects on global cognitive functions, but the underlying molecular mechanisms are still poorly understood. The present study aimed to investigate whether NBP mediates synaptic plasticity and blood–brain barrier (BBB) function, which play a pivotal role in the pathogenesis of vascular dementia (VaD), in a mouse model of bilateral common carotid artery stenosis (BCAS). Methods NBP was administered to model mice at a dose of 80 mg/kg by gavage for 28 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…Therefore, VD's development and therapeutic effect can be predicted by evaluating and dynamically observing the changes in antioxidant molecules in VD patients. IL-1β is highly expressed in serum, frontal cortex and hippocampus of VD patients, which may play a signi cant role in the mechanism of neuroin ammation [31,32]. The results of ELISA in this study showed that compared with Group Sham, the SOD activity in the serum of rats in Group VD decreased.…”
Section: Immunohistochemical Resultsmentioning
confidence: 52%
“…Therefore, VD's development and therapeutic effect can be predicted by evaluating and dynamically observing the changes in antioxidant molecules in VD patients. IL-1β is highly expressed in serum, frontal cortex and hippocampus of VD patients, which may play a signi cant role in the mechanism of neuroin ammation [31,32]. The results of ELISA in this study showed that compared with Group Sham, the SOD activity in the serum of rats in Group VD decreased.…”
Section: Immunohistochemical Resultsmentioning
confidence: 52%
“…Existing studies indicated that NBP may ameliorate the loss of TJ proteins through the downregulation of autophagy levels in human brain microvascular endothelial cells in the oxygen–glucose deprivation model (Wu et al 2020 ). The HIF-1α/MMP signaling pathway, which is related to the expression of tight junction proteins, has been reported to be suppressed by NBP in the BCAS model (Che et al 2023 ). Third, inflammatory markers might play a part in NBP’s positive effect on the cerebral endothelium, which needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In dementia, LTP is commonly inhibited; thus, stimulating or extending LTP may aid in restoring learning and memory functions ( Paoletti et al, 2013 ). In dementia subtypes such as AD and VaD, synapses display functional deficits, including reductions in synapse numbers, impaired dendritic spine morphology, and diminished neurotransmission capabilities ( Piscopo et al, 2022 ; Che et al, 2023 ).…”
Section: Pharmacological Effects Of Saponin Compoundsmentioning
confidence: 99%